2006
DOI: 10.1002/app.24948
|View full text |Cite
|
Sign up to set email alerts
|

Poly(trimethylene terephthalate) nanocomposite fibers comprising different organoclays: Thermomechanical properties and morphology

Abstract: Poly(trimethylene terephthalate) (PTT) nanocomposites were synthesized by in situ polymerization at high temperature with two thermally stable organoclays: 1,2-dimethylhexadecylimidazolium-montmorillonite (IMD-MMT) and dodecyltriphenyl phosphonium-MMT (C 12 PPh-MMT). PTT hybrid fibers with various organoclay contents were melt-spun at various draw ratios (DRs) to produce monofilaments. The thermomechanical properties and morphologies of the PTT hybrid fibers were characterized using differential scanning calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In 2002, the use of nanoclays has emerged as an interesting way for developing multifunctional textiles when polyamide‐6 clay nanocomposite multifilament yarns were produced by Bourbigot et al6 Indeed, the authors demonstrated a decrease of about 40% of the heat release rate (HRR) of knitted structures made with polyamide‐6 nanocomposite compared to the virgin polyamide. Many researchers were therefore interested in the development of nanocomposite fibers based on several polymer matrices such as polyamide‐6 (PA‐6),7–9 polybutylene terephtalate (PBT),10–12 polytrimethylene terephtalate (PTT),13–15 polyethylene terephtalate (PET),14, 16, 17–20 polylactide (PLA),21, 22 polyethylene (PE)23, 24 or polyimideamide (PIA) 25, 26…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, the use of nanoclays has emerged as an interesting way for developing multifunctional textiles when polyamide‐6 clay nanocomposite multifilament yarns were produced by Bourbigot et al6 Indeed, the authors demonstrated a decrease of about 40% of the heat release rate (HRR) of knitted structures made with polyamide‐6 nanocomposite compared to the virgin polyamide. Many researchers were therefore interested in the development of nanocomposite fibers based on several polymer matrices such as polyamide‐6 (PA‐6),7–9 polybutylene terephtalate (PBT),10–12 polytrimethylene terephtalate (PTT),13–15 polyethylene terephtalate (PET),14, 16, 17–20 polylactide (PLA),21, 22 polyethylene (PE)23, 24 or polyimideamide (PIA) 25, 26…”
Section: Introductionmentioning
confidence: 99%
“…But the organic modifier must have excellent thermal stability due to the high temperature (usually up to 2808C) that it has to withstand during the synthesis and process of PET. Many efforts have been done to search thermal stable MMT organic modifiers [5,8,26,29,[32][33][34][35][36][37], for alkyl ammonium cations, which are usually used in nylon/clay nanocomposites, have been proved unsuitable for the synthesis of PET/MMT composites. The decomposition of alkyl ammonium cations under high temperature not only alters the interface between the filler and the matrix polymer, but also induces the degradation of the polyester, resulting in deteriorated properties and undesirable color [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Due to some advanced properties, such as enhanced tensile and flexural strength, and thermal and barrier properties, a number of studies on PTT matrix have been carried out. [7][8][9][10][11] The crystallization of PTT matrix blends has also been reported, such as PTT/PC, [12] PTT/PEI, [13] and PTT/ABS. [14] Liu et al [15] successfully prepared PTT/clay nanocomposite via meltblending, and the results suggest that the introduction of nanosize clay layers accelerates the crystallization rate of PTT.…”
Section: Introductionmentioning
confidence: 99%